Residual stress generation during laser cladding of steel with a particulate metal matrix composite - Plati, A; Tan, J; Golosnoy, I; Persoons, R; van Acker, K; Clyne, T (2006)
Laser cladding is used to coat and repair the surface of various components. A significant issue relating to optimisation of the process is the generation of residual stresses. These are affected by the high thermal gradients inherent in the process, and associated differential thermal contraction. These stresses can lead to various types of distortion. A customised 3-D finite element model has been developed, incorporating these effects, based on simulation of conductive, convective and radiative heat transfer, and assuming elastic-perfectly plastic deformation behaviour. Creep effects have been neglected and the cladding (particulate metal matrix composite) has been treated as a continuum. Comparisons are presented between measured and simulated thermal fields and specimen deflection histories. The results indicate that the main features of residual stress generation in this type of system have been captured in the model. Implications for process optimization and control are briefly discussed. © 2006 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.